Testing for protonitazene in human hair using LC-MS-MS - Kintz, Pascal; Ameline, Alice; Gheddar, Laurie; Pichini, Simona; Mazoyer, Cédric; Teston, Katy; Aknouche, Frédéric; Maruejouls, Christophe (Journal of analytical toxicology, 2024)
Protonitazene is a synthetic benzimidazole opioid of the nitazenes class, developed in the 1950s as an effective analgesic, but never released on the market due to severe side effects and possible dependence. Despite its increasing use as a new psychoactive substance starting in 2019, its detection in human hair of intoxicated and deceased consumers has never been reported. We present the development and validation of a specific procedure to identify protonitazene in hair by liquid chromatography with tandem mass spectrometry. Drugs were incubated overnight at 40°C in 1 mL borate buffer, pH 9.5 with 20 mg pulverized hair and 1 ng/mg fentanyl-d5 used as internal standard. Drugs were then extracted with a mixture of organic solvents. The chromatographic separation was performed using an HSS C18 column with a 15-min gradient elution. Linearity was verified from 1 to 100 pg/mg. The limit of detection was estimated at 0.1 pg/mg. No interference was noted from a large panel of natural and synthetic opioids, fentanyl derivatives, or other new synthetic opioids. Protonitazene was identified at 70 and >7600 pg/mg in the whole head hair specimens of two male subjects deceased from an acute drug overdose in jail. Protonitazene was also identified at 14 and 54 pg/mg in two living co-prisoners. As nitazenes represent a growing threat to public health in various parts of the world, this method was developed in response to the challenges posed by the identification of this class of substances.